Factors Influencing Fraud Prevention In The Management Of Village Fund Allocations - Yanti, Sri; Hafni, Diska Arliena (Jurnal Akuntansi Terapan dan Bisnis, 2025)
Fraud is an act of fraud committed intentionally to obtain personal gain and cause harm to other parties without their knowledge. This study aims to determine whether the internal control system, individual morality and love of money affect the prevention of fraud in the allocation of village funds. This research uses a quantitative descriptive approach with purposive sampling technique. The sample consisted of the Village Head, Village Secretary, Head of Finance, Head of Planning and General Affairs and the Village Consultative Body from 16 villages in Manisenggo District, Klaten Regency. The data were collected through a questionnaire with a Likert scale and analyzed using IBM SPSS 24. The results show that the internal control system and love of money have no effect on fraud prevention, while individual morality does. Future research is recommended to increase the number of samples and variables so that the results obtained are more optimal and relevant.